2023
DOI: 10.1186/s40644-023-00556-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of PET/CT in the detection of liver metastases in well-differentiated NETs

Abstract: Background The aim of this retrospective study was to compare the diagnostic accuracy of somatostatin receptor (SSR)-PET/CT to liver MRI as reference standard in the evaluation of hepatic involvement in neuroendocrine tumors (NET). Methods An institutional database was screened for “SSR” imaging studies between 2006 and 2021. 1000 NET Patients (grade 1/2) with 2383 SSR-PET/CT studies and matching liver MRI in an interval of +3 months were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…In a large study of 728 NET patients, [ 68 Ga]Ga-DOTA-TATE PET/CT showed high sensitivity, specificity, accuracy, positive predictive value, and negative predictive value (97.0%, 95.1%, 96.6%, 98.5%, and 90.4%) in the detection of overall NET lesions [ 11 ]. Specifically identifying hepatic involvement in NET patients, similar high diagnostic accuracy was reported for SSR-PET/CT compared to the reference standard liver MRI with a sensitivity of 97.0% and a specificity of 97.7%, a PPV of 99.0% and NPV of 93.0% [ 12 ]. Moreover, SSR-PET/CT was found to have an important value in the diagnosis of pulmonary neuroendocrine tumors (carcinoids) and its distant metastases [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 58%
“…In a large study of 728 NET patients, [ 68 Ga]Ga-DOTA-TATE PET/CT showed high sensitivity, specificity, accuracy, positive predictive value, and negative predictive value (97.0%, 95.1%, 96.6%, 98.5%, and 90.4%) in the detection of overall NET lesions [ 11 ]. Specifically identifying hepatic involvement in NET patients, similar high diagnostic accuracy was reported for SSR-PET/CT compared to the reference standard liver MRI with a sensitivity of 97.0% and a specificity of 97.7%, a PPV of 99.0% and NPV of 93.0% [ 12 ]. Moreover, SSR-PET/CT was found to have an important value in the diagnosis of pulmonary neuroendocrine tumors (carcinoids) and its distant metastases [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 58%
“…Based on the WHO 2022 classification, which accounts for proliferation index (Ki-67) and mitotic information, NETs are categorized into well-differentiated neuroendocrine tumor (NET) grades G1, G2, and G3, and poorly differentiated small and large cell neuroendocrine carcinoma [20]. G1/G2 NETs exhibit high expression of somatostatin receptors on their cell membrane (80-95%) [21]. However, somatostatin receptor-based PET/CT is highly sensitive in detecting G1/G2 but G2 may be less sensitive in tumors with higher Ki-6 [21].…”
Section: Tumor Characterization and Guidelines For Locoregional Thera...mentioning
confidence: 99%
“…G1/G2 NETs exhibit high expression of somatostatin receptors on their cell membrane (80-95%) [21]. However, somatostatin receptor-based PET/CT is highly sensitive in detecting G1/G2 but G2 may be less sensitive in tumors with higher Ki-6 [21].…”
Section: Tumor Characterization and Guidelines For Locoregional Thera...mentioning
confidence: 99%
“…Daher wird in aktuellen Empfehlungen auch im Rahmen der PET/CT nach Möglichkeit die Durchführung einer Mehrphasen-CT empfohlen [72]. In einer größeren retrospektiven Arbeit mit 1000 Patienten wurde die Sensitivität und Spezifität der SSA-PET/CT mit der multiparametrischen MRT in insgesamt 2383 Untersuchungen verglichen [73]. Die patientenspezifische Sensitivität und Spezifität der SSA-PET/CT für die Detektion hepatischer Metastasen lag bei 97 bzw.…”
Section: Somatostatin-rezeptor-gerichtete Somatostatin-analogaunclassified